Additive allometric model of Quercus spp. stand biomass for Eurasia - Andreevich Usoltsev, Vladimir; Reza Shobairi, Seyed Omid; Petrovich Chasovskikh, Viktor (Ecological Questions, 2020)
When using the unique in terms of the volume of database on the level of stand of the genus Quercus, the trans-Eurasian additive allometric models of biomass of stands for Eurasian Quercus forests are developed for the first time, and thereby the combined problem of model additivity and generality is solved. The additive model of forest biomass of Quercus is harmonized in two ways: it eliminated the internal contradictions of the component and the total biomass equations, and in addition, it takes into account regional differences of forest stands not only on total, aboveground and underground biomass, but also on its component structure, i.e. it reflects the regional peculiarities of the component structure of biomass.